Analysis of a thermostable lipase from CTG-clade yeast: molecular expression, characterization and structure prediction - Mustaffa Kamal, Nurfarahain; Mohd Shariff, Fairolniza; M. Normi, Yahaya; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Malaysian Society for Microbiology, 2022)
Aims: This study was aimed to express Meyerozyma guilliermondii strain RT lipase using Komagataella phaffii X-33 expression system and its biochemical characterization and analyse the predicted structure of the product. Methodology and results: Meyerozyma guilliermondii strain RT obtained from the previous study was used as the source of RT lipase gene. Extracellular M. guilliermondii strain RT lipase expression has significantly been improved up to 56 U/mg at 24 h cultivation in Yeast extract-Peptone-Dextrose (YPD) medium containing (in w/v): 1% yeast extract, 2% peptone, 2% dextrose with 0.5% v/v methanol induction. Characterization of RT lipase showed optimum activity at 45 °C and pH 9. It exhibited stability in the alkaline pH range (8 to 10) and retained 50% of its residual activity at 30 °C for 30 min. Substrate specificity analysis revealed that it preferred short to medium-chain triacylglycerols (C2-C12) with the highest activity towards caprylic acid (C8). Pairwise alignment revealed three substitutions (S2L, S92L and S193L) present in non-CTG-clade hosts (K. phaffii). Homology modelling (YASARA) was used to predict the structures of RT lipase [wild type (wt) and recombinant (rc)]. Mutational analysis of the structures showed the differences in loops that might attribute to the reduction of the optimum temperature from 75 °C (wt) to 45 °C (rc). Conclusion, significance and impact of study: RT lipase was successfully overexpressed extracellularly using K. phaffii expression system with 91.8-fold higher specific activity than the native host. The conceptual advances on the importance of codon optimization before expressing a protein from a CTG-clade species in a non-CTG-clade yeast have been highlighted and the effect of the rare codon usage in recombinant protein characteristics has been evident.